2023
DOI: 10.3389/fnins.2023.1192786
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol and tetrahydrocannabinol exposure: Effects on spatial and working memory

Abstract: IntroductionAlcohol and cannabis are widely used recreational drugs that can negatively impact fetal development, leading to cognitive impairments. However, these drugs may be used simultaneously and the effects of combined exposure during the prenatal period are not well understood. Thus, this study used an animal model to investigate the effects of prenatal exposure to ethanol (EtOH), Δ-9-tetrahydrocannabinol (THC), or the combination on spatial and working memory.MethodsPregnant Sprague–Dawley rats were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 107 publications
0
0
0
Order By: Relevance
“…Notably, significant behavioral effects on the Morris water maze were only seen among female subjects (Lei et al, 2023), in contrast with the present study that found changes in interneurons in both sexes. Nevertheless, there are some parallels between drug effects on Morris water maze performance and hippocampal interneuron pathology.…”
Section: Con Clus Ionscontrasting
confidence: 99%
See 2 more Smart Citations
“…Notably, significant behavioral effects on the Morris water maze were only seen among female subjects (Lei et al, 2023), in contrast with the present study that found changes in interneurons in both sexes. Nevertheless, there are some parallels between drug effects on Morris water maze performance and hippocampal interneuron pathology.…”
Section: Con Clus Ionscontrasting
confidence: 99%
“…It is interesting that prenatal THC exposure (particularly alone) produced some of the most robust changes in SOM cells. On the Morris water maze, littermates exposed to prenatal THC showed the most severe impairments in spatial learning and memory (Lei et al, 2023). In addition, the pattern of significant changes in NPY cells exposed to either prenatal THC or alcohol alone, but not the combination, is also consistent with changes in anxiety-related behaviors (thigmotaxis) within the Morris water maze (Lei et al, 2023), as subjects exposed to either drug alone were more thigmotaxic, but those exposed to the combination were least thigmotaxic.…”
Section: Con Clus Ionsmentioning
confidence: 75%
See 1 more Smart Citation
“…We selected male mice because prior studies indicated that synaptic plasticity [55] and hippocampal function in males [56][57][58], but not females [55,58], were altered by PCE. Likewise, previous studies suggest PCE impairs spatial memory in males [58,59] but not females [58], though a more recent study revealed a deficit in females [60]. We will address sex as a biological variable in future studies.…”
Section: Discussionmentioning
confidence: 83%